Assessing the interspecies relationship betweenPseudomonas aeruginosa and Staphylococcus aureus in mixed biofilms grown in alginate beads and collagen scaffolds. Issue 5 (27th May 2022) - Khalid, Ammara; Beeton, Michael; Maddocks, Sarah
Abstract : Polymicrobial biofilms in chronic infected wounds harbour different bacterial species that interact with each other, competing or co-operating to survive. The two most common pathogens co-isolated from chronic wound biofilms are Pseudomonas aeruginosa and Staphylococcus aureus. Evidence from in vitrobiofilms models have shown these two bacteria interactand data suggests that P. aeruginosa inhibits the growth of S. aureusin mixed biofilms. This study aimed to assess the growth of these two species in a complex polymicrobial biofilm in a 3D matrix comprised of either alginate (1.5% w/v) or a collagen scaffold. Using a five-species biofilm (S. aureus, P. aeruginosa, Citrobacter freundii, Enterococcus faecalisand Escherichia coli), with all bacteria inoculated at time zero, it was consistently observed that P. aeruginosa was not recoverable over a 72h period, with sampling every 24h. However, P. aeruginosagrew well if it was added to a pre-formed four-species biofilm. Further, P. aeruginosa was seen to inhibit the growth of S. aureus after 24h subsequent co-culture in the pre-formed biofilm, which resulted in the emergence of small colony variants of S. aureus. Interestingly when P. aeruginosawas co-inoculated in a four species biofilm that did not contain S. aureus, its growth was not inhibited, suggesting a competitive interaction between these two bacteria during establishment of the early biofilm. These data were consistent in alginate beads and collagen scaffolds. In a chronic wound P. aeruginosais regarded as a late coloniser and the phenomena observed in this study might be reflective of this.